乳がんサバイバーの運動と服薬 - 山内, 英子 (Tairyoku kagaku. Japanese journal of physical fitness and sports medicine, 2018)
The incidence of breast cancer is rising in Japan year by year; and seems to peak at a younger age range compared to Western countries. About one half of breast cancer patients in Japan are diagnosed in their 30s to 50s. Among the cancers that frequently occur during the most productive years of life, breast cancer is considered the most serious one for survivors. Breast cancer treatments consist of surgery, hormone therapy, chemotherapy and radiation therapy. However, since all of these treatments have potential side effects, patients often stop taking therapy due to the side effects. To prevent and minimize such side effects, exercise plays a very important role. Furthermore, gaining excess weight for survivors has a negative impact on their prognosis. Thus, it is important that appropriate exercise and weight control interventions are developed.